Approaches to the Construction of Endocyclic Sulfoximines - Dobrydnev, Alexey V. (SynOpen, 2025)
Endocyclic sulfoximines are a relatively novel class of cyclic sulfoximines where the S(O)=N group is a part of a ring structure. They possess unique physicochemical and structural features, including three-dimensionality and chirality, amid chemical and thermal stability. This graphical review presents a comprehensive compilation of synthetic approaches toward endocyclic sulfoximines, organized by the type of reaction employed. The reaction conditions are presented in a detailed manner; the proposed reaction mechanisms and the catalytic cycles are also provided.
Keywords: sulfoximines; S–N bonds; heterocycles; cyclization; catalysis; chirality